THE USE OF LEARNING RESOURCES TO CULTIVATE CHARACTER VALUES ON STUDENTS - Riyanto, Riyanto; Aryulina, Diah (TRIADIK, 2017)
Abstract. Deviant behavior in Indonesia nation occurs in almost all aspect of life and in all institution whether informal, formal, or not formal. The cause of the problem is that ethics have not been applied yet. Ethics of a nation is rooted on nation character values. These values need to be cultivated to overcome the nation problem. Values cultivation can be conducted through nation character education. Nation character education can use learning resources because learning is an interaction between students and learning resources. Varying learning resources include messages, persons, materials, tools, techniques, and character with considering several aspects. Utilization of these learning resources is important to provide variation in character education learning process. Therefore learning process becomes easier, fascinating, fun, and undull. The purpose of this article was to study learning resources that are appropriate in cultivating student character. The study method used was literature review. Result of the study can be concluded that the use of learning resources is effective to cultivate character values to students.Keywords: Character values, learning resources